Characteristics, determinants and management of farmer-predator conflict in a multi-use dryland system, South Africa - Drouilly, Marine Justine (Department of Biological Sciences, 2020)
Extensive livestock farming provides an important source of food and fibre for humans and is often the only commercially viable land use in the more arid regions of the globe. Pastoralism can however lead to natural habitat degradation, fragmentation of landscape by fencing and conflict between livestock farmers and predators. Collectively these impacts have been identified as major threats to biodiversity in general and predators in particular. In the semi-arid Central Karoo region of South Africa, extensive small-livestock farming is the primary use of land and provides local predators with a plentiful supply of unguarded, easy-to-catch sheep in addition to permanent artificial water sources. The result is a widespread and pervasive conflict between farmers and predators and amongst diverse stakeholders on how to best manage both livestock and predators to reduce such conflict. A major impediment to understanding human-predator conflict on farmland and its impacts on biodiversity is the paucity of relevant applied research. Most research on mesopredators in South Africa has been conducted in protected areas (PA) or at the level of a single farm, precluding the generalisation of results to broader regions, and therefore limiting our understanding of the conflict on farmlands more generally. In this thesis I sought to better understand farmer-predator conflict in the Karoo region of South Africa with an emphasis on measuring the impacts of livestock farming on wildlife in general and how predators in particular impact livestock. I hypothesized that ecological, environmental and socio-economic factors would all contribute to the negative interactions between predators and small-livestock farmers, and to the persistence of the two most prevalent predators in the region, the black-backed jackal (Canis mesomelas) and the caracal (Caracal caracal), despite sustained lethal control. I addressed this hypothesis by first using camera trapping surveys to compare wildlife species richness on farmland with a nearby and similar-sized PA to assess the impacts of small-livestock farming on wildlife diversity and occupancy, notably predators. I then used scat analysis to compare the diet of jackal and caracal with those of conspecifics living in the PA to understand whether predators on farmland are targeting livestock or simply including them opportunistically in their diet. I also used Global Positioning System (GPS) clusters from collars affixed to mesopredators to determine whether jackal and caracal actively kill versus scavenge on livestock. Finally, I performed spatially-explicit interviews using semistructured questionnaires with farmers to assess the distribution and severity of the conflict with jackal, caracal and chacma baboon (Papio ursinus), to explore the potential environmental and socio-economic drivers of reported livestock losses, the attitudes to predators and the use of lethal methods to control predators. Contrary to predictions, species richness was similar on farmland and the PA while community structure, diversity and composition all differed with land use. Species richness and probability of use both varied with environmental factors but not with human disturbance. Diet differed markedly for jackal and caracal between the two land uses, with micromammals and plants dominating mesopredator diet in the PA and livestock on farmland. By combining the results of the biodiversity surveys with the diet analysis, I was able to assess prey preference by predators on medium and large iv vertebrates. The results revealed that while both jackal and caracal consumed more livestock on farmland than wild prey, only jackal showed a preference for livestock. The results of scat and GPS cluster analyses were consistent reinforcing the findings that mesopredators actively killed livestock on farmland but not from within the PA, even when individuals crossed onto neighbouring farms. Survey results showed that farmers perceive the severity of the conflict with jackal, caracal and baboon to be increasing, especially since the 2000s. There was a positive relationship between perceived livestock losses and both environmental (e.g. terrain ruggedness) and socio-economic (e.g. decrease in farm worker numbers) factors. Surprisingly, negative attitudes towards jackal and caracal were not significantly linked to the percentage of lamb losses but rather to their belief that predators should be confined to PAs. Tolerance was best explained by the perceived aesthetic appeal of both jackal and caracal. Finally, I showed that farmers preferred to use lethal versus non-lethal control methods to manage predation, including poison, because non-lethal methods were considered to be expensive, unpractical, labour intensive and less effective. The use of poison was driven by ecological (e.g. having jackal, caracal and baboon as the top three predators on the farm) and socio-economic (e.g. decrease in farm worker numbers) factors. Together, my results suggest that jackal and caracal, like many other mesocarnivores worldwide, display a remarkable ability to adapt to human-modified landscape, using both rangeland and the PA to feed on a diverse range of prey species. Even if small-livestock farms in the Central Karoo still host important components of indigenous biodiversity, the lack of government support and incentives to protect wildlife, the changes in farming practices, the associated increase in natural habitat from which predators can recolonise commercial farmland, and the reduced labour force may together result in farmers increasing their reliance on non-selective lethal control methods to protect their livestock. Of particular concern is the widespread use of illegal poisoning. If we are to find an appropriate balance between farming and conserving biodiversity on farmland, then a new approach will be required to this very old problem. Resource-constrained conservation authorities will need to be backed by multi-stakeholders’ engagements. Farmers will need to be supported through funds to increase farm worker numbers on farms and through improved livestock husbandry measures based on scientific research conducted at the appropriate temporal and spatial scales. The conflict between predators and farmers in the Karoo is complex and multifactorial, involving environmental, ecological, and socioeconomic factors. Finding solutions to limit its impacts is a societal decision at the crux of the debate between conservation and development and requires better use of available funding and multidisciplinary teams to tackle the issue.